Pengaruh Konsentrasi Dan Lama Inkubasi Kolkisin Terhadap Duplikasi Kromosom Planlet Terung (Solanum melongena L.) Haploid Galur Aksesi Hasil Kultur Antera - Sopian Zayid; Agus Surya Mulya; Yana Taryana (Fakultas Pertanian Universitas Winaya Mukti, 2021)
The purpose of this study was to determine the effect of colchicine on chromosome duplication and to determine the best colchicine concentration and incubation time for haploid eggplant chromosome duplication results from anther culture. Laboratory experiments have been carried out at PT. East West Seed Indonesia, Benteng Village, Campaka District, Purwakarta from March to June 2020. With an altitude of 69 m above sea level. The environmental design used in this study was a completely randomized design consisting of 7 treatments and repeated 4 times. Colchicine treatment design A = Control, B = colchicine 0.05% 24 hours incubation, C = colchicine 0.05% 48 hours incubation, D = colchicine 0.1% 24 hours incubation, E = colchicine 0.1% 48 hours incubation, F = kolkisisn 0.15% incubation 24 hours, G = colchicine 0.15% incubation 48 hours. The responses observed were contamination, callous plantlets, rooted plantlets, live plantlets, haploid plantlets, double haploid plantlets, triploid plantets and unreadable ploidy check results. The results showed that the colchysis concentration and incubation time had an effect on the duplication of haploid eggplant plantlet chromosomes resulting from anther culture. And giving colchicine at a concentration of 0.05% with an incubation time of 48 hours and a colchicine concentration of 0.1% with an incubation time of 48 hours had a significant effect on the double haploid plantet of 23.44%.